2018
DOI: 10.5194/angeo-36-741-2018
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting dynamics of electrons and protons in the near-Earth plasma sheet during dipolarization

Abstract: Abstract. The fortunate location of Cluster and the THEMIS P3 probe in the near-Earth plasma sheet (PS) (at X ∼ −7-−9 R E ) allowed for the multipoint analysis of properties and spectra of electron and proton injections. The injections were observed during dipolarization and substorm current wedge formation associated with braking of multiple bursty bulk flows (BBFs). In the course of dipolarization, a gradual growth of the B Z magnetic field lasted ∼ 13 min and it was comprised of several B Z pulses or dipola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 86 publications
(124 reference statements)
4
27
0
Order By: Relevance
“…At R < 12 R E , the occurrence peak shifts slightly to earlier MLTs for ions and to the later MLTs for electrons. Malykhin et al () have found the difference between proton behavior and electron behavior near 9 R E in the postmidnight region. It is possible that the diversion between ions and electrons can occur well beyond geosynchronous orbit.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…At R < 12 R E , the occurrence peak shifts slightly to earlier MLTs for ions and to the later MLTs for electrons. Malykhin et al () have found the difference between proton behavior and electron behavior near 9 R E in the postmidnight region. It is possible that the diversion between ions and electrons can occur well beyond geosynchronous orbit.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Thus, it is appropriate to ask the question, to what extent individual localized dipolarizations integrate into a large-scale dipolarization of the inner magnetosphere characteristic of the substorms expansion (Kepko et al, 2015)? A closely associated question, whether the so-called substorm current wedge (SCW) is composed of individual wedgelets, has received significant attention recently (Birn et al, 2011;Birn & Hesse, 2014b;Forsyth et al, 2014;Liu et al, 2015Liu et al, , 2018Malykhin et al, 2018;Palin et al, 2016;Sergeev et al, 2000). Panov et al (2016) used a fortuitous alignment of magnetospheric spacecraft and ground-based magnetometers and imagers to infer that during a weak substorm (the AE index was about 100 nT) the substorm dipolarization could have been produced by a single BBF.…”
Section: Introductionmentioning
confidence: 99%
“…During the prolonged "secondary" dipolarizations the increases in fluxes of suprathermal electrons, protons and heavy ions are often observed (Nosé et al, 2000;Apatenkov et al, 2007;Asano et al, 2010;Grigorenko et al, 2017;Malykhin et al, 2018a, b). Malykhin et al (2018b) studied the dynamics of fluxes and energy spectra of suprathermal electrons during the prolonged dipolarizations and showed that electrons can be accelerated by a betatron mechanism up to ∼ 90 keV. On the contrary, the behavior of ion energy spectra indicates the nonadiabatic character of ion acceleration in the course of dipolarizations (e.g., Nosé et al, 2000;Grigorenko et al, 2017;Malykhin et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%